Pengaruh Antibakteri Ekstrak Etanol Kulit Manggis (Garcinia Mangostana Linn) Terhadap Zona Hambat Bakteri Streptococcus Sanguinis Dominan Gingivitis (Kajian In Vitro) - Fadhilah, Laili Nur, drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K), drg. Retno Sari (2014)
Background: Garcinia mangostana linn was a medicinal plant. The main compound, xanthone, that consist in mangosteen pericarp had a capability of anti-bacterial activity. Purpose: This research's objective was to find out the antibacterial effect of ethanol extract of Garcinia mangostana linn against inhibiting zone of Streptococcus sanguinis bacteria. Method: Genuine experimental laboratory research with post only control group design method. The mangosteen pericarp treated by maceration method of extraction produce ethanol solvent. Anti-bacterial effort activity of the solvent tested using Kirby-Bauer disk diffusion method at 2%, 8%, 16%, 32% concentration, combined with negative and positive control of 0.2% chlorhexidin. Result: The ethanol extracted from mangosteen pericarp (Garcinia Mangostana Linn) arranged at 2%, 8%, 16%, 32% concentration could impede Streptococcus sanguinis bacteria from growing. The average diameter of inhibiting zone of each concentration is 3.05 mm, 3.98 mm, 4.88 mm, 6.38 mm, using ANOVA one way test at sigma score 0.000 (p<0.05). Conclusion: Ethanol extract of mangosteen pericarp (Garcinia Mangostana Linn) have positive effect on inhibition zone of Streptococcus sanguinis bacteria via in vitro.